Review paper on Bronchiectasis - Lohani, Sudhir (Journal of Advances in Internal Medicine, 2012)
Bronchiectasis is characterized by dilatation of bronchi, airflow limitation and chronic infection/ inflammation. The aetiology, pathology and management are discussed in this review. It is vital that we distinguish bronchiectasis from other obstructive airways disease like Asthma and Chronic obstructive airways disease as management strategies are different. DOI: http://dx.doi.org/10.3126/jaim.v1i1.5839 Journal of Advances in Internal Medicine. 2012; 1(1): 39-42